Effect of ventilation on the thermal performance of tunnel lining GHEs. (25th January 2016) - Zhang, Guozhu; Xia, Caichu; Zhao, Xu; Zhou, Shuwei
Highlights: Thermal response field tests considering ventilation were carried out. A 3D numerical model of tunnel lining GHEs was built. The effect of ventilation on the thermal performance of tunnel lining GHEs was evaluated. Abstract: A tunnel lining ground heat exchanger (GHE) uses surrounding rock as heat source and transfers heat through absorber pipes buried in the tunnel lining. In order to evaluate the effect of ventilation on the thermal performance of tunnel lining GHEs, thermal response field tests considering ventilation were performed in Linchang tunnel, and a 3D numerical model of tunnel lining GHEs was built and verified with the field monitoring data. The study results show that (i) the ventilation has a significant influence on the temperature field of surrounding rock; (ii) the heat exchange rate rises exponentially as convective heat transfer coefficient (CHTC) increases, and it increases significantly with the decreasing thickness of secondary lining; (iii) the heat exchange rate presents a linear variation as the inlet temperature increases, the growth gradient of the heat exchange rate rises exponentially as the CHTC increases and decreases gradually with the running time increase.